The Required Voltage Compensation to Overcome the Effect of Changing Flux and Back-emf in Squirrel Cage Three Phase Induction Motor Drives - Ahmed, Adil Omar; Abdulrahman, Alaa M. (Sulaimani Journal for Engineering Sciences, 2020)
This paper demonstrates the design and development of decoupling method in vector control induction motor. Three-phase induction motor is one of the most electric devices which is widely used in industrial applications. One of the most problems at high power application is controlling the transient current to protect the motor from damage. Various control schemes have been used however vector control is the most promised one which is used nowadays for the control purposes. A motor model for 1.5kW three phase squirrel cage induction is chosen for the design. In vector control three phase current is represented with two phase which are d-axis and q-axis. At first, current control for each axis is designed, later decoupling between them is shown and described. Matlab Simulation is used to validate the design and to show the results.
Keywords: Induction motor; decoupling; 3-phase conversion